Vlachs’ identity and the challenges of World War II - Nistor, Ionuţ (Balcanica Posnaniensia. Acta et studia, 2015)
During the Second World War, the Aromanians had their own, different perspectives over the combatants and the political structure in the region. Some of them willingly adhered to the Italian project, supported the fascist army and liked the idea of a political-territorial organisation (their own state, Pind, or at least an Albanian-Romanian confederation) under the patronage of Rome. The existence of multiple power centres with particular interests and zealous leaders weakened the force of the discourse and damaged from the inside a state project which was doomed to fail anyway, in the conditions in which Italy seemed to have other plans. The presence of many groups and leaders who disputed their supremacy, legitimacy and representation had consequences on obtaining cultural and political rights on the territories organized by the Italians. The interventions of the Romanian government tried to answer some specific and immediate needs regarding food supplies or teaching materials, but they did not manage efficiently the material and human resources and could not stifle the local conflicts for power and money.